Flipping your classroom: using online resources to engage students - Shamchuk, Lisa (My University, 2013)
There is a trend sweeping the education sector right now: “flipping the classroom”. As a means of increasing student engagement and learning, instructors are assigning videos to view as homework, and then using in-class time for discussion and active learning activities, instead of lecturing. What exactly is ‘flipping the classroom’? How does it work? Does it really increase student engagement and learning? What resources can be used? A MacEwan University librarian will provide an overview of the ‘flipping the classroom’ concept, as well as give ideas for online video resources available via the Library and for free on the Internet.
Presented on August 28, 2013 at MacEwan University Faculty Development Day in Edmonton, AB.
Keywords: teaching techniques; flipped classroom